Structural-Guided Identification of Small Molecule Inhibitor of UHRF1 Methyltransferase Activity - Awal, Md Abdul; Nur, Suza Mohammad; Al Khalaf, Ali Khalaf; Rehan, Mohd; Ahmad, Aamir; Hosawi, Salman Bakr I.; Choudhry, Hani; Khan, Mohammad Imran (Frontiers in Genetics, 2022)
manifests the maintenance of DNA methylation mediated by interaction between its SRA domain and DNMT1 like epigenetic modulators. However, overexpression of UHRF1 epigenetically responds to the aberrant global methylation and promotes tumorigenesis. To date, no potential molecular inhibitor has been studied against SRA domain. Therefore, the study focused to identify the active natural drug-like candidates against SRA domain. A comprehensive set of in silico approaches including molecular docking, molecular dynamics (MD) simulation and toxicity analysis was performed to identify potential candidates. A data set of 709 natural compounds was screened through molecular docking where chicoric acid and nystose has been found showing higher binding affinities to SRA domain. The MD simulations also showed the interaction stability and in silico toxicity analysis has been found for drug as safety margin. In addition, chicoric acid possessed longer interaction time and higher 5000mg/kg LD50. Moreover, the global methylation level (%5mC) has been assessed after chicoric acid treatment was in HCT116 cancer cell line at different doses. The result showed 7.5 µM chicoric acid treatment reduced methylation level significantly. Thus, the study found the chicoric acid as a promising epidrug-like inhibitor against SRA domain of UHRF1 protein.